Industry segmentation under environmental pressure: an optimal approach - Dai, Feng; Liu, Jingxu; Liang, Ling (Technological and Economic Development of Economy, 2014)
Based on the Solow growth model, this paper builds a combinatorial model for economic growth under environmental pressure. Using the model, the optimal number of industries in an economy can be computed, and the “optimal number” can be regarded as a criterion for decision making concerning industry segmentation. This paper presents a critical value of the number of industries in an economy, which determines the economic output to grow (or not) after industry segmentation. The findings include the following: (1) technological progress and innovative growth cause an industry segmentation, and (2) industry segmentation is the primary approach to sustaining economic growth under environmental pressure.